Moteriškoji tapatybė Onos Pleirytės-Puidienės-Vaidilutės kultūrinėje laikysenoje ir kūryboje - Bleizgienė, Ramunė (Literatūra, 2015)
This paper analyses and discusses the problem of a feminine identity, as presented in the early works and the cultural position of Ona Pleirytė-Puidienė-Vaidilutė. The paper investigates the earliest writings of Vaidilutė, “Kada rauda siela” and her diary, where she wrote about her relationship with M. K. Čiurlionis. Woman presented here is active, mobile and searching for the purpose of life. The specific female experience, however, is not explicated. Man (brother, friend) is her traveling partner who helps her to search for the Truth. In her diary, man becomes the leader in their relationship and has the biggest influence on her, as she develops her identity as a writer. The reason for this change can be the change of the place where the relationship between woman and man conspire. The equal link is in the mythical place, but when it takes place in a concrete social situation, man always is a leader; he is the one showing the way to a woman. The list of the independent Lithuanians made by historian of culture V. Kavolis, which consists of more than thirty people, includes only two women. The paper states that the gender proportions in the list reinforces the idea that women were excluded from the history of culture twice; the first time, when they did not have the equal opportunity to participate in the official social life and the second time, when the cultural history itself was recorded.